Incorporation of mobile learning approaches in staff training / Ros A. Yahaya, Nor H. Mohamed and Mohd Khalid Abas. - Yahaya, Ros A.; Mohamed, Nor H.; Abas, Mohd Khalid (Universiti Teknologi MARA Cawangan Selangor, 2015)
Mobile devices in training offer a new horizon to help participants to get started with mobile learning in the venture to experience the learning process. Various research emphasize the opportunities and benefits of using mobile learning and simultaneously highlight the obstacles that organizations faced when designing and implementing training by mobile learning. The aim of this paper is to highlight the difficulty in getting more participation and full engagement from the generation Y staff. The traditional approach neglects to consider the different learning approaches of the Gen Y type of learners, their generational attributes and their values at the workplace. Future study should incorporate the use of other platforms such as Whatsapp™ or Instagram ™ among Gen Y.